Neonatal hearing screening in newborns of mothers diagnosed with toxoplasmosis during the prenatal period - da Silveira, Maiara Rodrigues; Anschau, Cassandra Caye; Saltiél, Debora Ruttke Von; Kochhan, Denise Saúde; Unchalo, Adriana Laybauer Silveira; Teixeira, Adriane Ribeiro (Seven Editora, 2024)
Objective: To analyze the results of Neonatal Hearing Screening (NHS) in newborns whose mothers were diagnosed with toxoplasmosis during the prenatal period. Methods: This is an observational, cross-sectional and retrospective study, carried out at a University Hospital in the south of the country. The sample included neonates who had toxoplasmosis as the only Risk Indicator for Hearing Impairment (RIHI). Transient Evoked Otoacoustic Emissions (TOAE) and Automatic Brainstem Auditory Evoked Potential (AABR) were used for audiological evaluation of the sample (test and retest). The study was approved by the Research Ethics Committee (REC) of the institution. Results: The sample consisted of 72 newborns, 30 (41.7%) females and 42 (58.3%) males. Of the 72 newborns screened, 18 (25%) were referred for retesting. Of these, only 13 (72.2%) attended the retest, and the final result was the presence of normal hearing thresholds. Conclusion: The results of the study indicate that, in the sample studied, most of the newborns evaluated passed the Neonatal Hearing Screening (NHS). Among those who failed and attended the retest stage, all presented a bilateral response in the TOAE and AABR examinations, and there was no need for referral for audiological diagnosis. DOI:https://doi.org/10.56238/sevened2024.018-061